Courier: A Collaborative Phone-Based File Exchange System - Karlson, Amy; Smith, Greg; Meyers, Brian; Robertson, George; Czerwinski, Mary (2008)
While people often carry mobile phones for communication purposes, they are generally underutilized as productivity tools, especially in the workplace. In this paper we present Courier, a system that leverages the storage capacity and communication capabilities of the mobile phone to facilitate the viewing and exchange of PC-based documents when users are away from their desks. We describe a formative evaluation of Courier’s use in a collaborative meeting setting and report on the results. While participants were enthusiastic about Courier overall, our study also highlighted usability issues that will require further refinement, such as users’ concerns with privacy, reliability and speed.